Building performance simulation for design and operation - Hensen, Jan; Lamberts, Roberto (New York, NY : Spon Press, 2011)
Effective building performance simulation can reduce the environmental impact of the built environment, improve indoor quality and productivity, and facilitate future innovation and technological progress in construction. It draws on many disciplines, including physics, mathematics, material science, biophysics and human behavioural, environmental and computational sciences. The discipline itself is continuously evolving and maturing, and improvements in model robustness and fidelity are constantly being made. This has sparked a new agenda focusing on the effectiveness of simulation in building life-cycle processes. Building Performance Simulation for Design and Operation begins with an introduction to the concepts of performance indicators and targets, followed by a discussion on the role of building simulation in performance-based building design and operation. This sets the ground for in-depth discussion of performance prediction for energy demand, indoor environmental quality (including thermal, visual, indoor air quality and moisture phenomena), HVAC and renewable system performance, urban level modelling, building operational optimization and automation.Produced in cooperation with the International Building Performance Simulation Association (IBPSA), and featuring contributions from fourteen internationally recognised experts in this field, this book provides a unique and comprehensive overview of building performance simulation for the complete building life-cycle from conception to demolition. It is primarily intended for advanced students in building services engineering, and in architectural, environmental or mechanical engineering; and will be useful for building and systems designers and operators. -- Cover.
Introduction to building performance simulation / Jan L.M. Hensen and Roberto Lamberts -- The role of simulation in performance based building / Godfried Augenbroe -- Weather data for building performance simulation / Charles S. Barnaby and Drury B. Crawley -- People in building performance simulation / Ardeshir Mahdavi -- Thermal load and energy performance prediction / Jeffrey D. Spitler -- Ventilation performance prediction / Jelena Srebric -- Indoor thermal quality performance prediction / Christoph Van Treeck -- Room acoustics performance prediction / Ardeshir Mahdavi -- Daylight performance predictions / Christoph Reinhart -- Moisture phenomena in whole building performance prediction / Jan Carmeliet ... [et al.] -- HVAC systems performance prediction / Jonathan Wright -- Micro-cogeneration system performance prediction / Ian Beausoleil-Morrison -- Building simulation for practical operational optimization / David E. Claridge -- Building simulation in building automation systems / Gregor P. Henze and Christian Neumann -- Integrated resource flow modelling of the urban built environment / Darren Robinson -- Building simulation for policy support / Drury B. Crawley -- A view on future building system modeling and simulation / Michael Wetter.
Includes bibliographical references and index.
Keywords: Buildings -- Performance -- Computer simulation